Correlation of Patient-Reported Outcome (PRO-2) with Endoscopic and Histological Features in Ulcerative Colitis and Crohn's Disease Patients. (2nd April 2020) - Dragasevic, Sanja; Sokic-Milutinovic, Aleksandra; Stojkovic Lalosevic, Milica; Milovanovic, Tamara; Djuranovic, Srdjan; Jovanovic, Ivan; Rajic, Sanja; Stojkovic, Mirjana; Milicic, Biljana; Kmezic, Stefan; Oluic, Branislav; Aleksic, Marko; et al.
Abstract : Background and Objectives . Determination of inflammatory bowel disease activity determines further therapeutic approach and follow-up. The aim of our study was to investigate correlation between patients' reported symptoms and endoscopic and histological disease activity. Methods . A cross-sectional study was conducted in consecutive newly diagnosed patients with inflammatory bowel disease in a tertiary care referral center. The initial evaluation included patient-reported outcome for stool frequency subscore and rectal bleeding. Endoscopic activity was determined using the Mayo scoring system for ulcerative colitis and the Simple Endoscopic Score for Crohn's disease. Histopathological activity was assessed using a validated numeric scoring system. Results . We included 159 patients (63 Crohn's disease with colonic involvement and 96 with ulcerative colitis). We found significant correlation between the Mayo endoscopic subscoring system and histology activity in ulcerative colitis, while no correlation was found in patients with Crohn's disease. Patient-reported outcome showed inverse correlation with endoscopic and histological activity in Crohn's disease (r s = − 0.67 ; r s = − 0.72 ), while positive correlation was found in ulcerative colitis (r s = 0.84 ; r s = 0.75 ). Interpretation and Conclusions . Patient-reported outcome is a practical and noninvasive tool for assessment of disease activity in ulcerative colitis patients but not in Crohn's disease.